Simulation environment of distance protection with ATP and foreign models - Fabian E, Renzo G.; Leao, Fabio Bertequini [UNESP]; Mantovani, J. R S [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper presents an interactive simulation environment for distance protection, developed with ATP and foreign models based on ANSI C. Files in COMTRADE format are possible to generate after ATP simulation. These files can be used to calibrate real relays. Also, the performance of relay algorithms with real oscillography events is possible to assess by using the ATP option for POSTPROCESS PLOT FILE (PPF). The main purpose of the work is to develop a tool to allow the analysis of diverse fault cases and to perform coordination studies, as well as, to allow the analysis of the relay's performance in the face of a real event. © 2011 IEEE.
Keywords: ANSI C; ATP; COMTRADE; foreign models; MODELS; numerical distance relay; power systems; protection systems; COMTRADE format; Distance protection; Distance relay; Interactive simulations; Oscillography; Post process; Protection systems; Simulation environment; Adenosinetriphosphate; C (programming language); Circuit simulation; Electronic data interchange; Models; Standby power systems; Computer simulation